Pelatihan Platform Low Code (OutSystems) untuk Developer dan Tester di PT Neuronworks Indonesia - Rosa Reska Riskiana; Dana Sulistyo Kusumo (I-Com: Indonesian Community Journal, 2024)
PT Neuronworks Indonesia, as a provider of information technology services, faces challenges in accelerating application development to meet increasingly complex client needs. To address this, a training session on the Low Code platform, OutSystems, was held on June 24-25, 2024. The goal of this activity was to enhance the efficiency of application development and equip developers and testers with practical knowledge of OutSystems. The implementation method included both theoretical sessions and hands-on practice, enabling participants to understand the features and functionalities of the platform. The training results showed that the participants have a good understanding of using OutSystems, although some difficulties in adapting to the new method were noted. This training demonstrates the importance of Low Code technology in accelerating the application development process, which can positively impact the competitiveness and innovation of PT Neuronworks Indonesia in the future